Water utilization strategy of tomato grown on east-west orientation in solar greenhouses revealed based on hydroxide isotopes - Furong Han; Lili Zhangzhong; Wengang Zheng; Jingjing Li; Kaili Shi; Yibo Wei (Agricultural Water Management)
East-west orientation is a strategy that significantly enhances mechanization level within solar greenhouse (SG). However, this orientation alters environmental parameter distribution, affecting soil water use in tomatoes. Hydrogen and oxygen isotopes (δ18O) is a stable isotope measurement for oxygen used to trace water movement, this research through δ18O to explored the dynamics of water movement across the environment, soil, and tomato under east-west orientation. Four ridges (R1, R2, R3, and R4) were arranged from south to north, to investigate the varying water utilization strategies of tomatoes across these ridges. Photosynthetically active radiation (PAR) is effective for plant photosynthesis. Crop evapotranspiration under standard conditions (ETc) refers to the amount of evapotranspiration to achieve full production under ideal conditions. The findings indicated that PAR was the primary influencing water utilization among various ridges, with the coefficient of variation in autumn and spring recorded at 57.19 % and 42.02 %, respectively. Path analysis revealed PAR as a critical determinant of ETc, with direct path coefficients of 0.866 and 0.567. Through the use of δ18O tracing, it was established that the main soil water supply layer of R1 and R4 ridges with low cumulative PAR was 0–20 cm, and soil water contribution rate was 47.3–82.5 %. Conversely, R2 and R3 ridges which get higher cumulative PAR, the main soil water supply layer was 0–40 cm, with a soil water contribution rate between 57.5∼69.8 %. These findings suggest that a tailored irrigation control method can be devised for east-west orientation, catering to the diverse growth requirements of tomato.